Analisis semiotik: representamen siswa dalam menyelesaikan operasi bilangan bulat - Hersiyati Palayukan; Suri Toding Lembang; Adriana Galla Situru; Septin Dwi Rapa; Heri Heri (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this research is to investigate and describe student representation in solving integer operations. The research method used is descriptive qualitative research method. The subjects in this study were 15 of 31 junior high school students. Each of them is 9 Iconic Subjects (SI), namely subjects whose settlements use Iconic Representations and 6 Symbolic Subjects (SS), namely subjects whose settlements use Symbolic Representations. This study found that there are two types of Representamen in students' semiotic processes in solving Integer problems, namely types of iconic Representamen and symbolic Representamen. Iconic representation types are sign types that have a similar relationship with the object they represent, while symbolic representation types have a convention or rule relationship with the object they represent.